2016 49th Hawaii International Conference on System Sciences (HICSS) 2016
DOI: 10.1109/hicss.2016.532
|View full text |Cite
|
Sign up to set email alerts
|

The Workarounds Process as a Source of Knowledge Creation and Management

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Organisations can respond to workarounds in different ways and choosing the right response depends on the context [4,5,21]. According to Boudreau et al [8], sharing workarounds can be seen as a process of knowledge management. Indeed, our results show that sharing workarounds may benefit the organisation.…”
Section: Workarounds As a Source Of Organisational Improvementmentioning
confidence: 99%
See 3 more Smart Citations
“…Organisations can respond to workarounds in different ways and choosing the right response depends on the context [4,5,21]. According to Boudreau et al [8], sharing workarounds can be seen as a process of knowledge management. Indeed, our results show that sharing workarounds may benefit the organisation.…”
Section: Workarounds As a Source Of Organisational Improvementmentioning
confidence: 99%
“…As healthcare professionals are frequently confronted with unpredictable situations, it happens that they deviate from procedure. So-called workarounds are defined as intentional deviations from prescribed practices [2,8]. They are often studied in relation to how prescribed practices are supported by information systems, and how these systems are used differently in practice [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this, a clearly stated process script is needed, because else no deviation from a de jure process model can be identified. Previous studies have shown that process mining could be used to detect workaround candidates ( Beerepoot, Lu, van de Weerd, & Alexander Reijers, 2021 ;Boudreau et al, 2016 ;Ejnefjäll & Ågerfalk, 2019 ;Weinzierl, Wolf, Pauli, Beverungen, & Matzner, 2022 ). Yet, there is a need for evaluating the effectiveness of process mining for analyzing workarounds in informal contexts, like those of many SMEs, that may lack de jure models.…”
Section: Introductionmentioning
confidence: 99%